2017
DOI: 10.1002/cnm.2842
|View full text |Cite
|
Sign up to set email alerts
|

A monolithic 3D‐0D coupled closed‐loop model of the heart and the vascular system: Experiment‐based parameter estimation for patient‐specific cardiac mechanics

Abstract: A model for patient-specific cardiac mechanics simulation is introduced, incorporating a 3-dimensional finite element model of the ventricular part of the heart, which is coupled to a reduced-order 0-dimensional closed-loop vascular system, heart valve, and atrial chamber model. The ventricles are modeled by a nonlinear orthotropic passive material law. The electrical activation is mimicked by a prescribed parameterized active stress acting along a generic muscle fiber orientation. Our activation function is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 61 publications
(106 reference statements)
2
94
0
Order By: Relevance
“…In particular, some works have highlighted the non-negligible effect of the feedback wave within a closed-loop circuit, see e.g. [31][32][33][34]. We have leveraged the knowledge available in the modeling literature to develop a novel closed-loop model for the cardiovascular system that includes sufficient elements to reproduce theoretically the BCG signal and predict changes in the signal associated with specific pathological conditions.…”
Section: Background and Related Workmentioning
confidence: 99%
“…In particular, some works have highlighted the non-negligible effect of the feedback wave within a closed-loop circuit, see e.g. [31][32][33][34]. We have leveraged the knowledge available in the modeling literature to develop a novel closed-loop model for the cardiovascular system that includes sufficient elements to reproduce theoretically the BCG signal and predict changes in the signal associated with specific pathological conditions.…”
Section: Background and Related Workmentioning
confidence: 99%
“…The pericardial model we propose is based on [36] and is sketched in figure 3. Using our code it was also already applied to a two-chamber geometry in [37]. It consists of a spring and a dashpot in parallel acting in normal direction to the epicardial surface.…”
Section: Modeling the Pericardiummentioning
confidence: 99%
“…We thus expect that a global value of k p = 0.1 kPa/mm for pericardial stiffness yields good results for a biventricular geometry with ±60 • fibers. This value was also used in [37], although it was not really analyzed there, e.g. with respect to MRI.…”
Section: Pericardial Stiffnessmentioning
confidence: 99%
“…Despite the wide range of (bi) ventricular modeling studies found in literature, no consistent approach in incorporating the effect of external tissue support into these models could be found (we considered a non‐exhaustive subset of (bi) ventricular modeling studies (published over the last decade) where generic kinematic BCs were used:). Overall, most studies adopted the practice to apply Neumann BCs on the endocardial surface and to constrain basal out‐of‐plane motion by constraining the basal nodes not to move along the basal surface's normal direction (be it using an exact or penalty‐method based Dirichlet BC).…”
Section: Currently Used Generic Kinematic Constraintsmentioning
confidence: 99%
“…These epicardial BCs range from constraining the epicardium not to move along the surface normal 22 or in the circumferential direction 37 to elastic constraints, 40,46 viscoelastic constraints, 22 or both elastic and viscoelastic constraints (Robin-type BCs). 42 A few studies also constrained the movement of the apex, in all directions 15,23,43 or only in the lateral directions. 19 Table 1 gives an overview of the variety in BCs we found in the studies considered.…”
Section: Currently Used Generic Kinematic Constraintsmentioning
confidence: 99%